Financing education in Sub-Saharan Africa today (Foro de Educacion, 2012)
As showed in another article in this same issue, the gap between countries in relation to education is still significant. The financing of education is one of the aspects that will require more attention in order to close this gap. MDG 2 and 3 were not be reached by about 50 countries (among them several middle income countries), and quality is low in at least hundred countries, so it’s urgent to demand to the governments of these countries and to donor and development agencies to make an extra effort beyond the one already made since the nineties.